Transportation Systems; The Main Factors Of Urban Macro Forms Developments - Hoseinzadeh, Maryam; Hazery, Pegah (The Turkish Online Journal of Design Art and Communication, 2016)
Urban macro forms developments depend very on Transportation Systems changes. This systems have a triple effects on congestion; styles and degrees of urban extension; social and morphological points and problems of it .There are at least four social – technical periods according to dominant transportation modes as the linear model of transportation: walking city ; tram city ; tracked city and rubber city . each of these periods have their special and unique features and affect the size and form of the cities according to their range or ability to increase the distance from origin to destination .The purpose of this article is evaluation of different transportation periods as the linear model of transportation according to their role in urban macro forms developments and offers that it is better for cities to use this model in the opposite direction. This research method is descriptive - analytical study based on a library and resource world and the result was that cities should attend more to transportation patterns of the past such as walking and cycling and also network rail transportations and attend to construction of dense urban neighborhoods and groups which reduce the need for transportation and handling.
Keywords: Transportation Systems; mixed of land uses; Ulaşım Sistemleri; karışık arazi kullanımlarının Kentsel makro formları; yoğun kentsel mahalleler; Urban macro forms, dense urban neighborhoods